Digital Banking Risks and Information Systems Audit Readiness: Lessons from Financial Institutions (gjstudies, 2020)
This research examines how financial institutions prepare for Information Systems audits in the context of rapid digital transformation, with particular focuson data protection challenges and system control gaps. Through comprehensiveanalysis of 156 financial institutions across North America, Europe, and Asia from2018 to 2020, this study identifies critical success factors and common vulnerabilities in IS audit readiness frameworks. The research develops a novel Digital AuditReadiness Assessment (DARA) model that quantifies institutional preparednessacross technological, organizational, and regulatory dimensions. Empirical resultsindicate that institutions with mature digital audit readiness frameworks experience52% fewer regulatory findings and 47% shorter audit remediation periods comparedto peers with underdeveloped approaches. The study reveals that data protectiongaps account for 68% of critical audit findings in digital banking environments, whilesystem control deficiencies represent the most significant operational risk. Findingsdemonstrate that successful audit readiness requires integrated approaches combining technological controls, organizational capabilities, and continuous monitoringmechanisms. This research contributes actionable insights for financial institutionsnavigating digital transformation while maintaining robust audit preparedness andregulatory compliance.